2020
DOI: 10.3390/cancers12113300
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Deterministic Evolutionary Trajectories of Clear Cell Renal Cell Carcinoma

Abstract: The emergence of clinical resistance to currently available systemic therapies forces us to rethink our approach to clear cell renal cell carcinoma (ccRCC). The ability to influence ccRCC evolution by inhibiting processes that propel it or manipulating its course may be an adequate strategy. There are seven deterministic evolutionary trajectories of ccRCC, which correlate with clinical phenotypes. We suspect that each trajectory has its own unique weaknesses that could be exploited. In this review, we have sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Then, targeting KIF11 would be an attractive complement to evolution-targeted therapy. Evolution-targeted therapy in ccRCC is a novel con-cept that relies on patient stratification according to the deterministic evolutionary trajectory of the tumour [23]. Currently there are 7 well described evolutionary trajectories in ccRCC according to the tumour's genomic characteristics, evolution mode, and clinical course [24].…”
Section: Discussionmentioning
confidence: 99%
“…Then, targeting KIF11 would be an attractive complement to evolution-targeted therapy. Evolution-targeted therapy in ccRCC is a novel con-cept that relies on patient stratification according to the deterministic evolutionary trajectory of the tumour [23]. Currently there are 7 well described evolutionary trajectories in ccRCC according to the tumour's genomic characteristics, evolution mode, and clinical course [24].…”
Section: Discussionmentioning
confidence: 99%
“…At present, molecularly targeted drug resistance is a huge challenge in achieving a better prognosis for advanced RCC [41]. Several studies have suggested that drug resistance results from the involvement of multiple factors such as tumor stem cells and the activation of other pathways [42]. PDGF is an angiogenic factor that can induce tumor angiogenesis and directly or indirectly promote the proliferation and migration of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, clear cell renal cell cancer (ccRCC) is the commonest, accounting for the majority of cancer-related deaths [ 2 ]. Since the early loss of function is uncommon in patients suffering from renal cell carcinoma, about one-third of patients have metastatic disease at diagnosis [ 3 ]. In addition, those with localized tumors have up to 40% risk of recurrence following complete resection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%